Monitoring studies of the ecological and hydrogeochemical situation in the zone of influence of technogenic objects of the mining and industrial complex of the Kalush-Holyn Potash Deposit - E. Kuzmenko; S. Bagriy; I. Chepurnyi; T. Chepurna (Екологічна безпека та збалансоване ресурсокористування)
The assessment of groundwater and surface water conditions in areas of depleted salt deposits is a crucial component of monitoring studies due to the significant anthropogenic impact of objects such as tailings ponds, sludge accumulators, and the Dombrovskyi Quarry. The aim of the study was to establish, based on real experimental data from hydrogeochemical analyses of long-term groundwater monitoring via a network of hydrogeological observation wells, the areas of groundwater salinisation in the Kalush mining and industrial region, to assess the dynamics of chemical and physico-chemical indicators, and to identify threats to the region’s ecological situation. The research stages included the systematisation of monitoring data for 2021-2023, the creation of digital cartographic layers and attribute databases with quantitative data on groundwater chemical composition, geoinformation modelling, and the development of salinisation maps of the Kalush mining and industrial region and the dynamics of the aquifer salinisation. In 2023, hydrogeochemical studies were conducted in the Kalush mining and industrial region with the collection of 25 samples from observation wells, the Dombrovskyi Quarry, sludge accumulators, and the Limnytsia River. Water mineralisation and chemical composition were analysed. The study results showed the highest levels of mineralisation in the waters of sludge accumulator No. 3 and tailings pond No. 2, where mineralisation levels exceeded maximum allowable concentrations by 140 and 110 times, respectively. Chloride and sulphate contents in these objects also significantly exceeded permissible standards. A comparison of data for 2022 and 2023 revealed a significant increase in pollutant concentrations in several wells, confirming the continued negative impact of anthropogenic objects. Meanwhile, water quality in the Limnytsia River remained stable. The value of the study lies in evaluating the environmental condition of groundwater in the Kalush mining and industrial region based on the systematisation of hydrogeochemical monitoring data through observation wells using geoinformation modelling approaches